Advanced Proton Conducting Ceramic Cell as Energy Storage Device. (30th May 2017) - Marrony, Mathieu; Dailly, Julian
Abstract : Ba-based protonic ceramic cell (PCC) was investigated under galvanostatic electrolysis and reversible Fuel cell / electrolysis cycles modes. Such PCC has been made by industrial wet chemical routes (tape casting and screen-printing methods) and by using NiO-BaCe0.8 Zr0.1 Y0.1 O3-δ (BCZY81) as anode material layer / BCZY81–ZnO (5 mol%) as electrolyte, Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF) – BCZY81) as air electrode and BSCF as current collector. The optimization of key parameters of both fuel cell and electrolysis operating conditions such as water feed content, fuel utilization, temperature operation allow to validating promising electrical cell performances (>0.25 W/cm², 0.7V under fuel cell mode; 0.5A/cm², 1.3V under electrolysis mode) and reliability during more than 3500 h with limited electrical degradation (<2%/kh) at 700°C. The evolution of on line Electrochemical Impedance Spectroscopy measurements reveals that the total electrical resistances of PCC are lower under electrolysis mode than under fuel cell mode, in particular the ohmic resistance (electrolyte). But in the same time, the polarization resistance of the cell (air electrode interface) is higher under electrolysis mode. With time, the combination of high temperature and water vapor pressure can induce negative reaction able to accelerate the Ba-based materials aging. In any case, such highlights pave the way to the use of PCC technology as high efficient energy storage candidate.